2016
DOI: 10.21037/tcr.2016.11.75
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Mdm2-p53 signaling axis in the DNA damage response and tumorigenesis

Abstract: The p53 tumor suppressor acts as a guardian of the genome in mammalian cells undergoing DNA double strand breaks induced by a various forms of cell stress, including inappropriate growth signals or ionizing radiation. Following damage, p53 protein levels become greatly elevated in cells and p53 functions primarily as a transcription factor to regulate the expression a wide variety of genes that coordinate this DNA damage response. In cells undergoing high amounts of DNA damage, p53 can promote apoptosis, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 249 publications
(238 reference statements)
1
49
0
Order By: Relevance
“…Since p53 protein is a substrate of USP10, we further evaluated p14ARF/CDKN2A which is a well-known tumour suppressor protein mediating oncogenic p53 activation. p14ARF binds to MDM2 and stabilizes p53 when there is DNA damage or cellular stress (39,40). Although, there are numerous reports about transcriptional silencing of the p14ARF/CDKN2A gene through DNA promoter hypermethylation in many cancers, Ko et al (14) have recently reported that c-Myc protein influences the stabilization of p14ARF by activating USP10 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Since p53 protein is a substrate of USP10, we further evaluated p14ARF/CDKN2A which is a well-known tumour suppressor protein mediating oncogenic p53 activation. p14ARF binds to MDM2 and stabilizes p53 when there is DNA damage or cellular stress (39,40). Although, there are numerous reports about transcriptional silencing of the p14ARF/CDKN2A gene through DNA promoter hypermethylation in many cancers, Ko et al (14) have recently reported that c-Myc protein influences the stabilization of p14ARF by activating USP10 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Although many proteins are directly involved in the regulation of p53 levels and functioning, it is generally accepted that MDM2 is the principal negative regulator of p53 (37). Serving as an E3 ubiquitin ligase of p53, MDM2 not only negatively regulates p53 activity through the induction of p53 protein degradation (38), but directly inhibits p53 trans-action on chromatin (39).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly assumed, in part on the basis of transfection and/or overexpression studies, that viral protein targeting of USP7 will negatively impact p53 expression, generally induced upon virus infection and replication and inhibitory to virus production. However, our own studies in the context of infected cells have failed to identify any USP7 binding-dependent effects of vIRF-1 and vIRF-3 on p53 levels in latently infected PEL cells and during lytic reactivation in these and/or HHV-8 Ï© iSLK cells; indeed, depletion of USP7, which regulates p53 stability through the relative deubiquitination of p53 and its E3 ubiquitin ligase MDM2 (29,52), while phenotypically significant in PEL latency and HHV-8 productive replication, did not detectably alter p53 expression (27). Also in the present study, p53 levels were indistinguishable between iSLK cultures infected with wild-type HHV-8 and mutated virus expressing USP7refractory vIRF-2.S 247 A (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…USP7 is a known deubiquitinase of both p53 and its E3 ubiquitin ligase MDM2, stabilizing both substrates via removal of K48-linked polyubiquitin adducts. When p53-and MDM2-targeting ATM kinase is inactive, the affinity of USP7 for MDM2 is higher than it is for p53; under conditions of DNA damage response activation, however, the reverse is true and p53 is stabilized by ATM phosphorylation of MDM2 (and associated MDMX/MDM4) and consequent reduced USP7 binding to the p53 regulator (29). The interactions of all HHV-8 vIRFs with USP7 suggest that p53 regulation, and the resulting apoptotic inhibition, is a common node of vIRF activity in the context of infection.…”
mentioning
confidence: 99%